2006
DOI: 10.1024/0300-9831.76.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin K Variability Affects International Normalized Ratio (INR) Coagulation Indices

Abstract: Patients taking warfarin and consuming markedly changing amounts of vitamin K may have a variable weekly INR with potentially unstable anticoagulant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 29 publications
3
41
0
1
Order By: Relevance
“…Previous studies reported that as there was knowledge gap of the healthcare team with regard to warfarin-nutrient interactions which can lead to disruption in anticoagulant outcomes [8,24,25]. The finding of our study also showed that only 75.6% of the respondents answered correctly on the effect of taking large amount of leafy green vegetables (which are enrich with vitamin K), on warfarin.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies reported that as there was knowledge gap of the healthcare team with regard to warfarin-nutrient interactions which can lead to disruption in anticoagulant outcomes [8,24,25]. The finding of our study also showed that only 75.6% of the respondents answered correctly on the effect of taking large amount of leafy green vegetables (which are enrich with vitamin K), on warfarin.…”
Section: Discussionsupporting
confidence: 43%
“…Even relatively small increases in vitamin K intake (150 µg/day in vitamin K-replete patients or 25 µg/day in vitamin K-depleted patients) will lower the INR [21,22]. A prospective study of 43 anticoagulated patients found that changes in vitamin K intake and variability in INR correlated and that a weekly change of 714 µg of vitamin K would alter the INR by 1 unit [24]. These data highlight the sensitivity of the therapeutic window of warfarin anticoagulation to alterations in diet.…”
Section: Discussionmentioning
confidence: 99%
“…Out-of-range INR values can be a result of genetic predisposition, dietary modifications, drug interactions, and poor adherence [7][8][9]. Accordingly, it is important to evaluate patient adherence to warfarin because it is one of the modifiable factors and at the same time the evaluation can stimulate a better understanding of warfarin utilization and barriers to proper warfarin use.…”
Section: Introductionmentioning
confidence: 99%